The Effect of Water Intake during Pregnancy on Birth Weight - Tria Rosemiarti; Hardinsyah Hardinsyah; Budi I. Santoso; Sudung O. Pardede; Parlindungan Siregar; Netta M. Putri; Ratu S. Hanifah (Indonesian Society of Obstetrics and Gynecology, 2023)
Abstract Objective: This systematic review aimed to investigate the effect of water intake during pregnancy on infant birth weight. Methods: A comprehensive search was conducted using the keywords "water intake," "dehydration," "pregnancy," "outcome," "hydration," "birth weight," and "birth outcome" in databases such as "SCOPUS," "EBSCO," "PUBMED," "COCHRANE," and through "Google Search." MeSH headings "pregnancy" and "hydration" were used for the search. Inclusion criteria encompassed pregnant women without pathological disorders, birth weight as a studied outcome, prospective cohorts, clinical trial study designs, and Englishlanguage papers. Out of the 254 articles retrieved, six met the specifi ed requirements and were included in this review. Results: The fi ndings from the six studies consistently demonstrated a positive correlation between higher water intake, improved hydration, and increased birth weight. All studies measured water consumption or hydration status between 8-37 weeks of gestation. Regardless of the duration of the studies, underhydration or low water intake was consistently associated with lower birth weight. Conclusion: This review highlights that increasing water intake among pregnant women positively affects infant birth weight. Adequate water intake during pregnancy is recommended to be in the range of 2180 - 3000 mL daily, considering hydration status and the stage of pregnancy. Keywords: birth weight, hydration, pregnancy, water intake. Abstrak Tujuan: Untuk mengungkap pengaruh asupan air selama kehamilan terhadap berat lahir bayi. Metode: Menggunakan kata kunci "water intake," "dehydration," "pregnancy," "outcome," "hydration," "birth weight," dan "birth outcome,", artikel dicari. Data diambil dari database "SCOPUS," "EBSCO," "PUBMED," "COCHRANE," dan "Google Search". Kami menggunakan MeSH headings kehamilan dan hidrasi untuk istilah pencarian. Kriteria inklusi adalah perempuan hamil tanpa kelainan patologis, berat badan lahir adalah salah satu luaran penelitian, desain studi berupa kohort prospektif dan uji klinis, serta artikel dalam bahasa Inggris. Dari 254 artikel yang diperoleh, enam artikel memenuhi persyaratan dan digunakan untuk review ini. Hasil: Dari keenam penelitian menunjukkan bahwa semakin tinggi asupan air, semakin baik hidrasi atau asupan air meningkatkan berat bayi lahir. Semua penelitian mengukur konsumsi air atau status hidrasi antara 8-37 minggu. Studistudi ini secara konsisten memberikan bukti bahwa asupan air yang rendah atau kondisi kekurangan cairan dikaitkan dengan berat badan lahir rendah, terlepas dari durasi studi. Kesimpulan: Kajian ini menunjukkan bahwa peningkatan asupan air ibu hamil berpengaruh positif terhadap berat lahir bayi. Asupan air yang cukup pada ibu hamil adalah 2180 - 3000 mL setiap hari bergantung pada status hidrasi dan usia kehamilan. Kata kunci: asupan air, berat lahir, hidrasi, kehamilan.